2012
DOI: 10.1016/j.toxlet.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of particulate matter on the cardiovascular system

Abstract: Human exposure to particulate matter (PM) elicits a variety of responses on the cardiovascular system through both direct and indirect pathways. Indirect effects of PM on the cardiovascular system are mediated through the autonomic nervous system, which controls heart rate variability, and inflammatory responses, which augment acute cardiovascular events and atherosclerosis. Recent research demonstrates that PM also affects the cardiovascular system directly by entry into the systemic circulation. This process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(109 citation statements)
references
References 71 publications
(74 reference statements)
2
104
0
3
Order By: Relevance
“…The effects on the cardiovascular system can be elicited through both direct and indirect pathways (Nelin et al, 2012). TiO 2 NPs may affect the cardiovascular system directly by entry into the systemic circulation.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The effects on the cardiovascular system can be elicited through both direct and indirect pathways (Nelin et al, 2012). TiO 2 NPs may affect the cardiovascular system directly by entry into the systemic circulation.…”
Section: Tablementioning
confidence: 99%
“…As NPs possess smaller sizes, larger surface-to-volume ratio compared with particles of larger sizes of the same chemical composition, they exhibit improved penetration to cells, catalytic activity, higher biological activity (Johnston et al, 2013;Oberdorster, 2010;Oberdorster et al, 2005;Savolainen et al, 2010). In recent years, epidemiological and toxicological studies have demonstrated a positive association between airborne particulate matter (PM) and adverse cardiovascular effects Nelin et al, 2012;Polichetti et al, 2009), especially for fine ( 2.5 mm) (Weichenthal et al, 2014) and ultrafine ( 100 nm) particles (Karottki et al, 2014). Toxicity evaluation of engineered nanomaterials also showed that inhaled NPs can directly or indirectly pose adverse health consequences for the cardiovascular system Duan et al, 2013;Simeonova and Erdely, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Evidences showed that PM 2.5 was verified as having a causal relationship with CVDs which could increase the morbidity and mortality of CVDs and aggravate myocardial ischemia (Nelin et al 2012). In addition, PM 2.5 could induce the oxidative stress and inflammatory response through the blood vessels and cardiovascular system (Nemmar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological and toxicological studies have shown that ultrafine particles (UFPs) could contribute to adverse health effects, more than the larger particles (PM 2.5 , PM 10 ) (Donaldson et al, 2001(Donaldson et al, , 2005Hatzis et al, 2006;Mills et al, 2009;Murr and Garza, 2009;Oberdorster, 2000;Peters and Wichmann, 2002;Pope and Dockery, 2006;Stolzel et al, 2007). Other studies revealed that ultrafine particles can efficiently penetrate the respiratory system, including the central nervous system and the blood circulation system (Nel et al, 2006;Nelin et al, 2012;Nemmar et al, 2002;Oberdorster et al, 2004). In urban street canyons, the emission of UFPs combined with the limited dilution, makes them, 'hot spots' of particulate pollution, particularly of UFPs (Weber et al, 2013).…”
Section: Introductionmentioning
confidence: 99%